Avaliação comparativa de sistema de plantio com mola convencional e mola pneumática na linha de semente - Lauxen, Richard Dal Forno (2025)
The advancement of technologies applied to seeding has sought to meet a growing demand for greater efficiency and precision in agricultural operations. Among the innovations, pneumatic springs stand out, allowing for finer adjustments of the pressure exerted on the seed row. This study aims to compare the performance of pneumatic and mechanical springs, considering parameters such as deposition depth, seed deposition uniformity, and emergence. The methodology involves field trials with variations in load and speed, recording data on seed positioning and initial plant development. The results showed that the pneumatic spring system presented better performance in plant emergence and greater uniformity of seed deposition compared to the mechanical spring. Pneumatic springs achieved emergence percentages between 80.64% and 100% of the plots and with less variation in the vertical coefficients of variation (6.1% to 23.4%), indicating greater operational stability compared to mechanical springs.